Konsep Keadilan Wali terhadap Hak Anak Yatim yang Dipoligami Perspektif al-Maṣlaḥah al-Mursalah - Risdayani Risdayani; Zulfiah Sam; Munira Munira (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the concept of guardian justice for the rights of polygamous orphans in the perspective of al-Maṣlaḥah al-Mursalah. This research uses a type of qualitative descriptive research using a normative approach and using a deductive analysis method. The results of the study show that: (1) the urgency of polygamy justice in Islam is preventing tyranny against wives, avoiding the punishment of Allah SWT. the pain on the Day of Judgment, avoiding divisions in the family, not making it easy in Allah's law. and stay away from polygamy if you not be able to do justice to all wives; (2) the concept of guardianship for orphans in Islamic law, namely the guardianship of orphans is the same as the order of guardians in marriage; (3) the concept of guardian justice for the rights of polygamous orphans, namely that there is no difference in justice between polygamous orphans by their guardians and other women in terms of maintenance, clothing, shelter, night distribution and husband's kindness including giving dowry. The concept of guardian justice for the rights of polygamous orphans in the perspective of al-Maṣlaḥah al-Mursalah is carrying out polygamy procedures according to state law, namely the recording of polygamy in the Religious Courts which must be carried out by guardians who want to polygamy orphans under their guardianship for the benefit of personal, family and society.